A scoping review of urban design and planning studies on the Covid-19 pandemic and elements of the built environment - Boujari, Pouria; Ghamar, Sarah; Nasirian, Mahdi; Ghapanchian, Fateme; Khajavi, Mahtab; Qasemi, Atieh; Bahari, Mohsen; Delavar, Yasin; Garrousi, Hamideh (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Human life has faced fundamental challenges in many aspects due to the spread of the Coronavirus disease in the world, resulting in rethinking urban design and planning policies and theories to make cities more resilient and healthier. Numerous studies have been conducted in this field due to the pivotal role of the built environment in improving public health. The present study aims to assess the role of the influential components of the built environment in the outbreak of Covid-19 by conducting a systematic literature review. The studies were searched through the Scopus database and screened and reviewed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Totally, 145 studies among 13,002 met the predetermined criteria. The results were expressed in 11 themes including mobility, density, soundscape, public spaces, green spaces, housing, land use, socio-economic qualities, environmental qualities, tourism, and smartness.